PENERAPAN PROBLEM SOLVING DALAM KOOPERATIF TIPE STAD UNTUK HASIL BELAJAR SMK MUHAMMADIYAH 2 PEKANBARU - Putri Clawson; Eggi Octanti (P3M STKIP 'Aisyiyah Riau, 2015)
This research was conducted with the aim to find out the increase in economic learning outcomes of students of class X ADP 3 at SMK Muhammadiyah 2 Pekanbaru through the application of problem solving methods in cooperative Student Team Achievement (STAD) types. The study was conducted during May 2015. The subjects of this study were students of class X ADP 3 SMK Muhammadiyah 2 Pekanbaru, which totaled 39 people, all of whom consisted of female students. Collecting data in this study using observation sheets of students, teachers, and learning outcomes through various tests. The results showed that student activity increased in each cycle. In cycle 1 the classification of student activity was classified as good at 81.02%. In cycle 2 the classification of student activity was classified as very good 89.74%. The increase in student learning outcomes led to an increase in student learning outcomes reaching the Minimum Learning Completion Standard (SKBM) 75, in cycle 1 of 89.7% with an average value of 88.3 classified as good. In cycle 2 student learning outcomes that reach the Minimum Learning Completion Standards (SKBM) 75, increased to 92.3% with an average value of 90.1. This marks the achievement of success that has been set in this study Minimum Minimum Mastery Standards (SKBM) 75 of at least 85% of the total number of students.